PENGARUH VARIASI DURASI CAMSHAFT TERHADAP UNJUK KERJA MOTOR BAKAR 4 LANGKAH - Putra, Feri Setya; Sanata, Andi; Muttaqin, Aris Zainul (ROTOR, 2013)
To obtain maximum engine performance one way to do is to do modification the camshaft . Changes can be made to alter or modify the time to open and close the valve. As already unknow that big power generated by the engine is affected by the amount of residual gases that exit the combustion chamber. The amount of air and fuel mixture entering the combustion gases and regulated by the duration of the opening and closing of the valve.For it was necessary to study the extent to which the effect of the change by the duration of the camshaft to the increased power and torque of the engine, which can then be recovered size is definitely the most appropriate duration to generate great power and torque. Effective power produced at 220 ° camshaft duration variation is at 6000 RPM of 7.7 HP, variations in camshaft duration 227 °, ie at 8.49 HP at 6500 RPM, variations in camshaft duration 233 °, ie at 6500 RPM at 8.77 HP, variations in camshaft duration 239 °, ie at 9.53 HP at 6500 RPM. Average turning moment - resulting in maximum average variation of camshaft duration 220 °, ie at 6000 RPM of 1.37 Nm Variations camshaft duration 227 °, ie at 6000 RPM 1.43 Nm Variations camshaft duration 233 °, ie at 1.47 Nm at 6000 RPM Variations camshaft duration 239 °, ie at 6500 RPM of 1.51 Nm Keywords: effect of variations in the duration of the camshaft, power, torque, and fc (fuel concumtion).